Surface characterization of feldspathic ceramic using ATR FT-IR and ellipsometry after various silanization protocols - Cavalcanti Queiroz, Jose Renato [UNESP]; Benetti, Paula [UNESP]; Oezcan, Mutlu; Cappa de Oliveira, Luiz Fernando; Della Bona, Alvaro; Takahashi, Fernando Eidi [UNESP]; Bottino, Marco Antonio [UNESP] (Elsevier B.V., 2012)
Objectives. This study characterized the feldspathic ceramic surfaces after various silanization protocols.Methods. Ceramic bars (2 mm x 4 mm x 10 mm) (N = 18) of feldpathic ceramic (VM7, VITA Zahnfabrik) were manufactured and finished. Before silane application, the specimens were ultrasonically cleaned in distilled water for 10 min. The ceramic specimens were randomly divided into nine groups (N = 2 per group) and were treated with different silane protocols. MPS silane (ESPE-Sil, 3M ESPE) was applied to all specimens and left to react at 20 degrees C for 2 min (G20). After drying, the specimens were subjected to heat treatment in an oven at 38 degrees C (G38), 79 degrees C (G79) or 100 degrees C (G100) for 1 min. Half of the specimens of each group were rinsed with water at 80 degrees C for 15 s (G20B, G38B, G79B, G100B). The control group (GC) received no silane. Attenuated total reflection infrared Fourier transform analysis (ATR FT-IR) was performed using a spectrometer. Thickness of silane layer was measured using a spectroscopic ellip-someter working in the lambda = 632.8 nm (He-Ne laser) at 70 degrees incidence angle. Surface roughness was evaluated using an optical profilometer. Specimens were further analyzed under the Scanning Electron Microscopy (SEM) to observe the topographic patterns.Results. ATR FT-IR analysis showed changes in Si-O peaks with enlarged bands around 940 cm(-1). Ellipsometry measurements showed that all post-heat treatment actions reduced the silane film thickness (30.8-33.5 nm) compared to G20 (40 nm). The groups submitted to rinsing in hot water (B groups) showed thinner silane films (9.8-14.4 nm) than those of their corresponding groups (without washing) (30.8-40 nm). Profilometer analysis showed that heat treatments (Ra approximate to 0.10-0.19 mu m; Rq approximate to 0.15-0.26 mu m) provided a smoother surface than the control group (Ra approximate to 0.48 mu m; Rq approximate to 0.65 mu m). Similar patterns were also observed in SEM images.Significance. Heat treatment after MPS silane application improved the silane layer network. Rinsing with boiling water eliminated the outmost unreacted regions of the silane yielding to thinner film thicknesses. (C) 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Adhesion; Ceramic; Silane coupling agent; Surface; Surface characterization